2013
DOI: 10.1007/s12594-013-0022-x
|View full text |Cite
|
Sign up to set email alerts
|

Geology and Geochemistry of Archaean Felsic Metavolcanic Rocks of the Eastern Part of the Kolar Greenstone Belt, Dharwar Craton, India: Implications for their Petrogenesis and Geodynamic Setting

Abstract: In the Kolar greenstone belt of the Dharwar craton, felsic metavolcanics are encountered prominently in its eastern region around Surapalli and Marikoppa. These felsic volcanic rocks are essentially homogeneous and their bulk mineralogy is almost the same. They consist of phenocrysts of quartz and feldspar, set in a fine-grained quartzo-feldspathic groundmass. They are calc-alkaline rhyolite in composition, and are characterized by high SiO2 (av. 75.74 wt.%), moderate Al2O3 (av. 11.84 wt.%), Na2O (av. 3.55 wt.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 55 publications
0
9
0
Order By: Relevance
“…The rocks are high magnesium basalts (MgO -12.5-20.1 wt.%) and are correspondingly enriched in Cr (254-876 ppm) and Ni (108-242 ppm). These rocks from the central part are more magnesian and less siliceous (Table 2a) than the high mg-basalts (referred as basaltic komatiites by Ugarkar et al, 2014) of northern part of Shimoga schist belt (Ugarkar et al, 2014). The studied high magnesium basalts are characterized by lower TiO 2 , Al 2 O 3 and K 2 O, and higher Fe 2 O 3 concentrations.…”
Section: Geochemistry Of Mafic Volcanic Rocks Of Bababudan and Chitradurga Groupsmentioning
confidence: 90%
See 1 more Smart Citation
“…The rocks are high magnesium basalts (MgO -12.5-20.1 wt.%) and are correspondingly enriched in Cr (254-876 ppm) and Ni (108-242 ppm). These rocks from the central part are more magnesian and less siliceous (Table 2a) than the high mg-basalts (referred as basaltic komatiites by Ugarkar et al, 2014) of northern part of Shimoga schist belt (Ugarkar et al, 2014). The studied high magnesium basalts are characterized by lower TiO 2 , Al 2 O 3 and K 2 O, and higher Fe 2 O 3 concentrations.…”
Section: Geochemistry Of Mafic Volcanic Rocks Of Bababudan and Chitradurga Groupsmentioning
confidence: 90%
“…These high magnesium rocks also have higher total REE contents and have slightly enriched chondrite-normalized REE patterns that are 18-24 times chondrite. In contrast, the basalts from the northern part of the schist belt are characterized by lower total REE and have flat REE patterns (Ugarkar et al, 2014). Primitive mantle-normalized patterns (Fig.…”
Section: Geochemistry Of Mafic Volcanic Rocks Of Bababudan and Chitradurga Groupsmentioning
confidence: 95%
“…The steep mylonitic zone, a major thrust-fault contact (Chitradurga Thrust Fault) along the eastern margin of the Chitradurga greenstone belt, extending over a length of 400 km from Gadag in the north to Mandya in the south is considered as the boundary between the two blocks (Kaila et al, 1979;Chadwick et al, 2000;Sengupta and Roy, 2012). The volcano-sedimentary association present in the greenstone terrains of the WDC and EDC displays distinct geodynamic settings, as deciphered by recent petrological and geochemical studies (Balakrishnan et al, 1999;Manikyamba et al, 2008Manikyamba et al, , 2014Manikyamba and Kerrich, 2011;Jayananda et al, 2013Jayananda et al, , 2014Ugarkar and Nyamati, 2002;Ugarkar et al, 2000Ugarkar et al, , 2013. Based on combined U-Pb zircon ages and Nd isotope data, the craton has been divided into three provinces western (3.4 to 3.2 Ga), eastern (3.4 to 3.2 Ga) and central with mixed old and younger crust (3.4 to 3.2 Ga and 2.56 to 2.52 Ga) and eastern with mainly younger (2.56 to 2.52 Ga) crust Jayananda et al, 2013).…”
Section: Regional Geologymentioning
confidence: 99%
“…The craton has been divided in to the western block and the eastern block, the boundary between them is demarcated by a steeply dipping mylonite zone traced along the eastern boundary of the Chitradurga greenstone belt [1][2]. Mafic to felsic metavolcanic sequences are encountered in the greenstone belts of both the blocks [1,[3][4][5][6][7][8]. In general, in the greenstone belts of the western block of the Dharwar craton, the felsic metavolcanics occur as a stratigraphic member of classic basalt-andesite-dacite-rhyolite (BADR) sequence.…”
Section: Introductionmentioning
confidence: 99%
“…Considerable amount of studies have been carried out on the mafic metavolcanics of the greenstone belts of the Dharwar Craton [9][10][11][12][13][14][15][16][17]. Ugarkar et al [18] have reported basaltic komatiites, tholeiitic basalts and tholeiite basaltic andesites from the northern part of the Dharwar-Shimoga belt.…”
Section: Introductionmentioning
confidence: 99%